Senior Tourism: a network science approach over the last twenty years through CiteSpace - Pestana, M.H.; Parreira, A. (Tourism and Management Studies International Conference, TMS Algarve 2018, 2018)
Adopting a co-authorship and co-citation network approach, the aim of this paper is to evaluate senior tourism research during the last twenty years and to discover structures in terms of leading papers, journals, authors, countries and institutions. The mapping of bibliometric data use CiteSpace. Data from Scopus build a network of 512 articles. The results reveal a slow increase of research, with the last period including 40.69% of outputs. The most co-cited papers are mainly older, represent 2.73% of the sample and account for 13.24% of citations. The authors with most publications are Jang M and King M, representing 1.95%. The co-cited journals show a core-periphery structure, where Tourism Management is ranked first. The co-authorship network reveals that major collaborative networks are based on geographical and institutional proximity, dominated by the United States. The keyword analysis demonstrates that motivation, attitude, satisfaction, experience, heritage and tourism management are significant areas of emerging research.